Pengembangan Sistem Informasi Inventaris dan Peminjaman Barang Berbasis Web untuk Meningkatkan Efisiensi dan Transparansi Pengelolaan Aset Desa - Yupi Kuspandi Putra; Muh. Adrian Juniarta Hidayat; Irwan Fakhrurrozi; Nurhidayati (Fakultas Teknik Universitas Hamzanwadi, 2026)
Inventory and item borrowing are important parts of asset management in schools, organizations, companies, and government institutions. The Gelanggang Village Office still uses a manual inventory and borrowing system, making it highly vulnerable to errors and inefficient processes. Inventory management is used to record and monitor all owned items so that their condition, quantity, and usage can be clearly identified. Meanwhile, the item borrowing system functions to regulate the use of goods by the village government for a certain period, ensuring that asset utilization is more organized and controlled. This study aims to develop a web-based inventory and item borrowing information system to minimize item damage and improve the efficiency, effectiveness, and transparency of village asset management. The method used in this research is the SDLC Waterfall model. The web-based system includes features for data management, transaction recording, approval processing, and automatic report generation. Testing using the Customer Satisfaction Index (CSI) with 30 respondents resulted in a score of 79.46% (categorized as “satisfied”), indicating that the system is capable of replacing manual recording with a faster and more accurate process. The system has proven feasible for use in Gelanggang Village and has the potential to become a model for the digitalization of inventory management in other villages, supporting technology-based governance.